By the Book : Murder Off the Books - Book 3 - Berry, Tamara (Naperville, Illinois : Poisoned Pen Press, 2023)
"Author Tess Harrow and her daughter, Gertrude, are starting to get a bad reputation due to their involvement in recent murder cases, so Tess has come up with the perfect plan to drum up some positive press. Shell combine her new book release and her bookstore opening into one big event, giving her a chance to wine and dine the locals and some big press contacts. But the night before the party, Tess is greeted by a surprise: her mother has come for a visit, with her much-younger new boyfriend in tow ... a boyfriend Gertrude recognizes as the notorious Levi Parker, a man recently connected to the deaths of three elderly widows. Tess immediately alerts Sheriff Boyd about the visitor, but its already too late. Levi Parker is found dead and Tesss mother is starting to look like the prime suspect. Bernadette swears she didnt murder Levi, and Tess is doing her best to maintain her mothers innocence, but too many coincidences keep stacking up. With the whole town seemingly against her family, its up to Tess to get to the bottom of the story before its too late"--
Keywords: Women novelists -- Fiction; Mothers and daughters -- Fiction; Murder -- Investigation; Fiction; Sheriffs -- Fiction; Cozy mysteries; Detective and mystery fiction; Novels